The opportunities of educating morality for children through samples of folklore - A.Sharaffitdinov; U.Yusupov (Genius Publishing Group, 2022)
This article explains in detail that the early moral development in childhood is shaped by the examples of folklore in the preschool age, and that this period is a solid foundation for a child's bright future.
Keywords: curiosity; need; activity; folklore